Neural Correlates of Contents and Levels of Consciousness - Overgaard, Morten; Overgaard, Rikke (Frontiers in Psychology, 2010)
Experimental investigations of the neural substrate of consciousness typically take one of two paths, studying 1) contents or 2) levels of consciousness. It seems obvious to most that these two “paths” are interrelated, yet much less obvious how. This paper gives one suggestion to grasp the interrelation, arguing that conscious levels are determined by conscious contents in a very specific way. It follows from the argument that conscious contents are so-called natural kinds, whereas conscious levels are not.